PENGARUH STRUKTUR MODAL, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 - Marcellia Mustika Maharani; Haerudin . (Universitas Muhammadiyah Semarang, 2019)
ABSTRACT This study is a banking company listed on the Indonesia Stock Exchange in the year 2013 until 2016. Method of determining the sample by purposivesampling method, with several criteria that have been determined then the numberof samples is as many as 29 banking companies. The research data is secondarydata obtained from Indonesia Stock Exchange (IDX). Data analysis usedregression analysis and path analysis using SPSS Version 16.0 program. Based on result of research of H1: with Capital Structure coefficient β1 equal to -1,272 with value of probability signification of Capital Structurevariable of its influence to Company Value of 0,0%, hence Capital Structure thereis no significant positive influence to Company Value. H2: with Profitabilitycoefficient of β2 equal to -546,001 with value of probability of significancevariable of Profitability influence to Company Value of 0.000, 0 henceProfitability no significant positive effect to Company Value. H3: with CompanyGrowth coefficient of β3 equal to 4,944 with significance value of CompanyGrowth Factor significance influence to Company Value equal to 0,072 (7,2%)<0,010 (10%), hence Company Growth have significant positive effect toCompany Value. H4: there is a simultaneous positive influence between theCapital Structure, Profitability, and Corporate Growth on Company Value in theBanking Company listed on the BEI in 2013-2016. Determination Coefficient (R2) value of 48.4% so that the potential research for other variables in research with the orientation of Corporate Valueof 51.6%. While the value of Standardized Coefficient that the priority variablesin a row are: Company Growth (13.50%), Capital Structure (-37.20%);Profitability (-57.40%);.